On the response of the U-Oscillating Water Column breakwater in the Port of Salerno for PTO installation (Proceedings of the European Wave and Tidal Energy Conference, 2025)
This article describes the characteristics of a U-Oscillating Water Column plant, named also REWEC3 (REsonant Wave Energy Converter), that has been realized in the Port of Salerno (Italy). The objective of the infrastructure is to enlarge the port basin area by taking advantage of the most recent developments in the field of caisson breakwaters. The building of the caissons was completed in 2022, when a monitoring activity started of three active chambers. In the paper, a general overview of the U-OWC caisson breakwater realized in situ in conjunction with the initial results of the response of the U-OWC pneumatic chambers useful for the characterization and the design of an optimized PTO (Power-Take-Off) to be coupled with the U-OWC device of the Port of Salerno